The Filipino and Latino managers: A comparative study of their value orientations - Uy, Arnel Onesimo O. (Animo Repository, 2012)
Few studies have explored value similarities and differences between private sector managers in Latin countries like Argentina, Colombia, Mexico, and Brazil and the Philippines. These countries were former colonies of either Spain or Portugal or both. In our study, we found that managers from the Philippines, Argentina, and Brazil were more alike as they were classified as possessing High Personal and High Moral value orientations, while managers from Colombia and Mexico were most alike as they possessed a High Personal and High Competence value orientations. We discuss the implications of these findings, limitations of the study, and make recommendations for further research. Copyright © 2012 De La Salle University, Philippines.